Post Tradisionalisme Islam : Dari Teologi Teosentrisme Menuju Teologi Antroposentrisme - Zuhairi Misrawi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2002)
This paper tries to explore the case that make the Moslem thought's back wardness as formulated in their theology. For centuries, muslim people disappear in theocentrism theology which lie the God over all. God is personificatied in both perceptions, in one hand shows his absolute power, but on the other hand sign his band to humanism characteristics. The developing theology then constitutes the theology that support the God and sink the human existence. As the problem solver of this case, the writer offers the anthropocentrism theology. This theology that the writer tries to explore the lost dimensions in religious doctrine that Allah as well as the heaven God, also the earth God. The anthropocentrism theology give the more cares to human problems. This theology also tries to change the religious knowledge fushuluddin as the knowledge of belief become the knowledge that suggest to the human being to do the change. At last, the anthropocentrism theology paradigm by the people of post traditionalist is the effort to explore the theocentrism bureaucracy theology that for a centuries dominates the religious thought. The anthropocentrism offer the base of cultural move which take along the democracy hope, civil society, and the pluralism.